One new Mexican Salacia with pedunculate inflorescences (Celastraceae, Salacioideae) - Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2019)
One new species of Salacia (Celastraceae, Salacioideae) with pedunculate inflorescences from Puebla, Mexico, is described: S. pueblana Lombardi. It is distinguished by its flat, canaliculate disc, papillose sepals, and flowers that dry yellowish-green. It resembles S. multiflora (Lam.) DC. subsp. multiflora by its slender branched inflorescence, but differs from it by its flower outline, disc, and sepals. Se describe una nueva especie de Salacia (Celastraceae, Salacioideae) de inflorescencias pedunculadas de Puebla, México: S. pueblana Lombardi se distingue por su disco aplanado y canaliculado, sépalos papilosos, y flores que se secan de color verde amarillento. Esta nueva especie se asemeja a S. multiflora (Lam.) DC. subsp. multiflora por su inflorescencia ramificada, pero se diferencia por el perfil de las flores, su disco y sépalos.
Keywords: Neotropics; New species; Puebla